Study of the Competencies of Cooperative Education Students: A Comparison among Employers, Instructors, and Cooperative Education Students from Prince of Songkla University, Phuket Campus - Sangtong, Kamonwan; Tongtep, Nattapong (Journal of Education Studies, Chulalongkorn University, 2024)
Prince of Songkla University, Phuket Campus, has a policy to promote cooperative education and work-integrated learning, emphasizing the importance of sending students to obtain practical work experience in order to prepare them for the real world. The research objective of this paper is 1) to analyze the evaluation results of cooperative education student from the perspectives of the employers, instructors, and cooperative education students, and 2) to compare three different perspectives on the competencies of cooperative education students. Data was collected by gathering student performance questionnaires from these three groups during the academic year 2022. Questionnaires were verified by professionals and responded by 104 employers, 64 instructors, and 164 students. Statistical analysis was conducted, including frequency distribution, mean calculation, and standard deviation. The research findings indicate that, overall, the cooperative education students’ competencies were perceived to be the highest by the instructors, less high by the employers, and lowest by the students themselves. The competencies that showed the most significant development across all perspectives were self-development in soft skills, hard skills, ethical and moral behavior, and adherence to organizational discipline. The area that showed most room for improvement, as perceived by instructors, was in the students’ ability to produce comprehensive and advanced reports. There was a consensus between the employers and the instructors that students had stronger development in hard skills than in soft skills. Therefore, it is recommended that the curriculum should focus more in future on enhancing students’ soft skills, to better meet the expectations of employers by developing graduates with higher competency and greater potential.